2019
DOI: 10.1016/j.nutres.2019.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Interventions involving a major dietary component improve cognitive function in cognitively healthy adults: a systematic review and meta-analysis

Abstract: 47Accumulating evidence suggests a role for diet in promoting brain health. The purpose of this 48 systematic review was to (i) quantitatively assess whether interventions with a major dietary 49 component can enhance cognition in cognitively healthy adults, and, (ii) identify responsive 50 domains of cognition to inform the design of future dietary trials. Electronic databases were 51 systematically searched to find eligible randomized controlled trials that assessed the effect of 52 interventions with a majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
(130 reference statements)
1
14
0
Order By: Relevance
“…Our results are in line with studies showing that higher adherence to the MedDiet is associated with cognitive scores and white matter integrity (Pelletier et al, 2015;Karstens et al, 2019). As for the cognitive scores, similar to that of McEvoy et al (2019), high MEDAS was associated with executive functioning but not with memory scores. These findings might be related to the age of our cohort as executive functioning appears to decline earlier than other cognitive domains (McEvoy et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in line with studies showing that higher adherence to the MedDiet is associated with cognitive scores and white matter integrity (Pelletier et al, 2015;Karstens et al, 2019). As for the cognitive scores, similar to that of McEvoy et al (2019), high MEDAS was associated with executive functioning but not with memory scores. These findings might be related to the age of our cohort as executive functioning appears to decline earlier than other cognitive domains (McEvoy et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…As for the cognitive scores, similar to that of McEvoy et al (2019), high MEDAS was associated with executive functioning but not with memory scores. These findings might be related to the age of our cohort as executive functioning appears to decline earlier than other cognitive domains (McEvoy et al, 2019). Our results also confirm that high adherence to the MedDiet was associated with lower diffusivity values, including MD and RD (Pelletier et al, 2015).…”
Section: Discussionmentioning
confidence: 65%
“…A meta-analysis encompassing 15 trials and 6480 participants demonstrated that diet interventions (primarily based on the adoption of a Mediterranean diet) improved performance on measures of global cognition, executive function, and processing speed during normal aging [ 221 ]. This is also supported by a systematic review of the evidence, which indicates that adherence to a Mediterranean diet is associated with better cognitive performance.…”
Section: Prevention Of Cognitive Decline Through Nutritional Interventionsmentioning
confidence: 99%
“…There is evidence that intervention to reduce some of these risk factors can delay or decrease the risk of age-related cognitive impairment or MCI (McEvoy et al, 2019;Ngandu et al, 2015;Petersen et al, 2014;Williamson et al, 2019). Physical activity is associated with protection from cognitive decline and dementia, and high-intensity exercise is associated with even greater protection (Livingston et al, 2017).…”
Section: Promising Non-pharmaceutical Treatment Strategies: Addressinmentioning
confidence: 99%